A case study of throwing motion of a male para- short stature javelin thrower - Yamate, Y.; Makino, M.; Mizuno, Y.; Ae, M. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of the present study was to investigate the throwing motion of a male para- short stature javelin thrower (F41) in a real competition using the 3D DLT method, compared with male able-bodied javelin throwers as reference. At the 119th Nippon Sport Science University Athletic Meet (March 27, 2021), one para- athlete who participated in the men's javelin throw was videotaped with two video cameras. The release parameters of javelin such as the initial velocity and projection angle at the release, and body segments angle were calculated for the only one trial, the best. The features of para-athlete were clarified by comparing them with the able-bodied javelin throwers (n=13) as reference. The release parameters of javelin showed that there was large difference in the horizontal velocity of javelin between the para-athlete and the reference throwers (12.59 and 19.35 m/s). The para-athlete of short stature in the present study showed the delayed withdrawal of the left leg at R-on, the delayed initiation of the rotation of the hips and trunk during throwing phase, and the left foot pointing to the right at L-on.